Sostenibilidad rural en Michoacán: políticas públicas para la gestión agroambiental - Ávila Rayo, María de la Luz (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
This thesis analyzes rural sustainability in the Mexican state of Michoacán, focusing on the Purépecha indigenous community of Santa Fe de la Laguna. Using an integrated and multidimensional approach, the research assesses the impact of environmental and agrarian public policies on local resource management, community development, and cultural identity preservation. The study employs qualitative methods, including interviews, surveys, and document analysis, complemented by context-specific indicators that measure environmental, agricultural, economic, and social dimensions. The findings reveal a disconnection between institutional frameworks and local realities, along with structural limitations in policy coordination across government levels. Nevertheless, the study also identifies community-led practices of resilience, self-management, and participation that contribute to sustainability from a territorial and cultural perspective. Based on these results, the thesis proposes strategies to redesign public policies through intercultural approaches, community engagement, and institutional integration, aiming to foster a more just, sustainable, and respectful model of rural development aligned with indigenous autonomy.

La presente tesis analiza la sostenibilidad rural en el estado de Michoacán, con énfasis en la comunidad indígena purépecha de Santa Fe de la Laguna. A partir de un enfoque integral y multidimensional, se evalúa el impacto de las políticas públicas agroambientales en la gestión local de los recursos naturales, el desarrollo comunitario y la preservación de la identidad cultural. Se emplearon métodos cualitativos, como entrevistas, sondeos y análisis documentales, complementados con indicadores adaptados al contexto comunitario para evaluar aspectos ambientales, agrarios, económicos y sociales. Los hallazgos revelan una desconexión entre los marcos normativos e institucionales y las realidades locales, así como limitaciones estructurales en la articulación de políticas públicas entre niveles de gobierno. Sin embargo, también se identifican prácticas comunitarias de resiliencia, autogestión y participación que fortalecen la sostenibilidad desde una perspectiva territorial y cultural. Finalmente, se proponen estrategias para rediseñar políticas públicas con enfoque intercultural, participación comunitaria e integración interinstitucional, orientadas a promover un modelo de desarrollo rural más justo, sostenible y respetuoso de la autonomía indígena.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2025-1229; Sostenibilidad rural; Comunidad indígena; Políticas públicas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19429